An investigation of the electronic structure and optical properties of Pd-doped SnO2 based on first principles - Dlear R Saber (Materials Research Express)
This study employs density functional theory (DFT) to investigate the impact of Palladium (Pd) doping on the structural, electronic, and optical properties of rutile tin oxide (SnO _2 ). In the analysis, Pd dopant atoms replaced Sn atoms, effectively shifting the rutile SnO _2 absorption edge closer to the visible light spectrum. The calculated band gap of 3.515 eV for pure rutile SnO _2 is in good agreement with experimental findings. The real and imaginary components of dielectric function show that absorption edges are relocated to the visible spectrum as a result of Pd-doping. This modification implies that Pd-doped SnO _2 has promise for photocatalytic applications because of its highest wavelength absorption coefficient. A red shift in the infrared absorption spectra was generated by decreasing band gaps and rising PDOS with increasing Pd content across all states. The influence of Pd atoms, particularly in the low-energy region, was confirmed by comparing the permeability of Pd-doped SnO _2 perovskite with other experimental and theoretical findings. These results clarify how Pd doping modifies the rutile SnO _2 performance, enabling its application in advanced photocatalysis.